Cryopreservation of platelets: an in-vitro comparison of four methods. Issue 1 (January 1981) - Taylor, M A
Abstract : Platelets were cryopreserved in four different cryoprotectives-two intracellular (dimethylsulphoxide, glycerol) and two extracellular (hydroxyethyl starch, dextran). The platelets were evaluated according to their yields, hypotonic shock response, and serotonin uptake, which are useful parameters for establishing optimum storage conditions. Hydroxyethyl starch and dextran were found to be poor cryoprotectives while 5% dimethylsulphoxide was the most suitable.